Web-Based Inventory Management System Using First In First Out Algorithm - Nazri, Syania Aldila; Fakhriza, M; Nasution, Adnan Buyung (Jurnal Penelitian Medan Agama, 2024)
PT. Agung Selaras Group is a property company that operates in the business of selling houses. With a good sales management system, the property company can support its work activities. The aim of this research is to develop a system that can simplify stock management and minimize the risk of loss in the sales process. The data source for this research was obtained from direct observation and interviews with PT. Agung Selaras Group. In this system the author will combine the First In First Out method in managing incoming and outgoing product stock. The results of this research are that the system that has been designed can make it easier for managers to collect data on incoming and outgoing goods so that the risk of managing product stock can be minimized, and with computerized reports it can provide more precise, accurate and fast information. From the results of black box testing, the percentage of this application system can run well.